Menggali Minat Beli Konsumen: Peran Kualitas Produk dan Harga Tahu Baxo Ibu Pudji - Hermawan Budiyanto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
In the increasingly fierce business competition, understanding the factors that influence consumer buying interest is crucial. This study analyzes the effect of product quality and price on consumer purchase intention of Tofu Baxo Ibu Pudji in Pamularsih, Semarang City. Using a quantitative survey method, data was collected from 50 respondents through questionnaires. The results showed that product quality and price have a strong and positive relationship with consumer buying interest. The correlation test shows that product quality has a calculated r value of 0.68 and price of 0.62, both of which are greater than r table (0.2787), indicating a significant relationship. Partial regression test (t-test) shows that product quality (t count = 38.83) and price (t count = 6.96) have a significant effect on purchase intention (t table = 2.01063). The simultaneous test (F-test) shows that product quality and price together have a significant effect on buying interest with an F value of 26.1168 (F table = 3.200). The coefficient of determination (R2) shows that product quality and price explain 52.63% of the variation in consumer buying interest, while 47.37% is influenced by other factors. The results of this study provide insight for business owners in improving quality and pricing strategies to increase competitiveness and sales volume.